Energy, exergy and economic analysis of a novel geothermal energy system for wastewater and sludge treatment. (1st September 2019) - Di Fraia, Simona; Macaluso, Adriano; Massarotti, Nicola; Vanoli, Laura
Highlights: A novel geothermal energy system for sewage sludge drying and electricity production is proposed. The energy, exergy and economic analysis is carried out for a case study. The system reduces sludge disposal by 70%, producing 1.68 kWh per kg of processed sludge. The proposed system has a simple payback of around 5 years and it avoids 662 tons per year of carbon dioxide equivalents. Abstract: Wastewater treatment is one of the most energy-consuming processes in the water sector, requiring both electric and thermal energy. In order to improve their sustainability, renewable energy sources can supply such energy demands in wastewater treatment plants, especially in small islands, where the lack of connections with mainland and environmental restrictions promote the use of unconventional fuels and technologies for energy production and waste treatment. For this reason, in this work, the use of geothermal energy is proposed for electric and thermal energy generation for wastewater and sludge treatment. An energy, exergy and economic analysis for the developed system is carried out. The study is carried out for a district wastewater treatment plant on the island of Ischia, in southern Italy, which presents diffused low-medium enthalpy geothermal sources, considered in this work to power an organic Rankine cycle system for electric energy production and to heat the desiccant flow for sludge drying. The proposed system reduces sludge to be disposed by around 70% and it covers 100% of the electrical energy demand of the wastewater treatment plant, with a production of 1.68 kWh per kg of processed sludge. Despite the high investment, the revenues deriving from the avoided sludge disposal and the electricity production, make the system convenient, with a simple payback of about 5 years and a saving of CO2 equivalent emissions equal to 628 tons/year. Therefore, the energy, exergy and economic analysis of the proposed system shows that the geothermal source is a viable and environmentally sustainable solution to produce electrical and thermal energy for wastewater and sludge treatment plants, especially in small islands or energy isolated systems, where electric energy supply and sewage sludge treatment are commonly critical challenges.